2017
DOI: 10.1001/jamaophthalmol.2017.2747
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Potentially Severe Retinopathy of Prematurity by Remote Image Grading

Abstract: IMPORTANCE-Telemedicine in retinopathy of prematurity (ROP) has the potential for delivering timely care to premature infants at risk for serious ROP. OBJECTIVE-To describe the characteristics of eyes at risk for ROP to provide insights into what types of ROP are most easily detected early by image grading. DESIGN, SETTING, AND PARTICIPANTS-Secondary analysis of eyes with referralwarranted (RW) ROP (stage 3 ROP, zone I ROP, plus disease) on diagnostic examination from the Telemedicine Approaches to Evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
1
1
Order By: Relevance
“…The infants in this study had older gestational age and higher birth weight which were different from previous studies [ 2 4 , 6 , 7 , 9 14 , 16 , 17 , 19 22 , 37 – 44 ]. This might reflect the neonatal care system in this region and might suggest the need for ROP screening in the older gestational age and higher birth weight infants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The infants in this study had older gestational age and higher birth weight which were different from previous studies [ 2 4 , 6 , 7 , 9 14 , 16 , 17 , 19 22 , 37 – 44 ]. This might reflect the neonatal care system in this region and might suggest the need for ROP screening in the older gestational age and higher birth weight infants.…”
Section: Discussioncontrasting
confidence: 99%
“…This study had similar results to the previous studies that supported the benefit of digital fundus photographic system to detect clinically significant ROP or ROP-RT [ 2 , 3 , 6 , 9 , 11 13 , 15 17 , 19 22 , 36 , 38 40 , 42 , 44 ] but our results had higher sensitivity, specificity, and LR+. The difference in instrumentation and images quality may contribute to these differences.…”
Section: Discussionsupporting
confidence: 91%
“…Although they are not direct comparisons, these studies inform us of the complexities in accurately diagnosing the individual components of severe ROP by both methods. Quinn et al also found that a substantial number of images revealed RW-ROP earlier than the diagnostic examination. The solution, it appears, lies in making telemedicine more robust, repeatable, and reproducible in capturing both prethreshold and treatable features of ROP, such that ROP specialists are confident that they can use this information in providing optimal treatment for these infants with ROP.…”
mentioning
confidence: 99%